Dual Role of Fas/FasL-Mediated Signal in Peripheral Immune Tolerance - Yamada, Akiko; Arakaki, Rieko; Saito, Masako; Kudo, Yasusei; Ishimaru, Naozumi (Frontiers in Immunology, 2017)
Fas-mediated apoptosis contributes to physiological and pathological cellular processes, such as differentiation, and survival. In particular, the roles of Fas in immune cells are complex and critical for the maintenance of immune tolerance. The precise pathways and unique functions associated with Fas/FasL-mediated signaling in the immune system are known. The dual character of Fas/FasL-mediated immune regulation that induces beneficial or harmful effects is associated with the onset or development of immune disorders. Studies on mutations in genes encoding Fas and FasL gene of humans and mice contributed to our understanding of the pathogenesis of autoimmune diseases. Here we review the opposing functions of Fas/FasL-mediated signaling, bilateral effects of Fas/FasL on in immune cells, and complex pathogenesis of autoimmunity mediated by Fas/FasL.